Strategi Pemberantasan Peredaran Narkoba Menuju Kabupaten Bungo Bersih Narkoba (Bersinar) - Yudhi Novriansyah; Herawati Herawati; Supriyati Supriyati; Darham Wahid; Bela Putra (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
To find the good solutions in order to eradicate drug trafficking in Bungo Regency, The Bungo Regency’s Government in collaboration with the members of studying socio-cultural issues at the Research and Community Service Institute (LPPM) of Muara Bungo University and under the direction of the Jambi Province National Narcotics Agency (BNNP Jambi) held a Focus Group Discussion (FGD) Strategy for Combating Drug Trafficking in Bungo District Towards Indonesia Bersinar 2045. This FGD’s activity involves several organizational elements that have a strategic position in the Bungo District community and are considered to have ideas and solutions to combat drug offenders by taking into conditions of the social environment and local wisdom culture.